THE ROLE OF SCHOOL PRINCIPALS IN IMPROVING TEACHER PERFORMANCE IN MUHAMMADIYAH KARANGTURI ELEMENTARY SCHOOL YOGYAKARTA - Tulaihah Ning Safitri; Muhammad Rizqi Hidayat (UIN Sumatera Utara Medan, 2019)
This study aims to analyze the role of school principals in improving the performance of elementary school teachers in Muhammadiyah Karangturi Yogyakarta, along with supporting and inhibiting factors in improving the performance of elementary school teachers in Muhammadiyah Karangturi Yogyakarta. This study uses qualitative research using descriptive-analytic methods. To get the data, researchers went directly in the field (field research). In analyzing data, researchers gradually use data reduction, data presentation, and data verification. Besides, in analyzing the performance of teacher-researchers using data indexing procedures. The results of this study indicate that the school principal in his role as the highest leader in this institution has a positive impact on improving the performance of elementary school teachers in Muhammadiyah Karangturi. This is evident that (a) The teacher is ready to implement the new curriculum. (b) The teacher uses learning strategies that are more creative and innovative. (c) The teacher can evaluate student learning by applicable curriculum requirements, namely in cognitive, affective, and psychomotor aspects. (d) The teacher teaches not only the material but also moral responsibility.